AUDIT SISTEM INFORMASI ABSENSI PADA PT. SUNAR REKA ARTHA MENGGUNAKAN FRAMEWORK COBIT 5 FOCUS DOMAIN MEA - Angelia, Adinda; rahmah, Nurul; Yulianto, Agus (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Sunar Reka Artha is a company that has a business in telecommunication contractor service. This is done with the intention of making it easy for its employees to avoid fraudulent acts or falsification of data related to absence of workers or employees. A tool that assists in recording employee attendance. In this study, the authors collected data in the form of questionnaires which were distributed to employees who used to use fingerprint machines. Then the data is audited using the Cobit Framework version 5 with Domain Monitor, Evaluate, and Assess (MEA). In order to reach the necessary conclusion, a number of suggestions were realized to optimize the capabilities and update to fingerprint machine and to able to upgrade to attendance system using a web-based online attendance application, at PT. Sunar Reka Artha in the future.